1994
DOI: 10.1128/iai.62.6.2149-2157.1994
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an elastinolytic metalloprotease from Aspergillus fumigatus and immunoelectron microscopic evidence of secretion of this enzyme by the fungus invading the murine lung

Abstract: Extracellular proteases have been suggested to be virulence factors in invasive aspergillosis. Since serine protease gene-disrupted mutants retain virulence, other proteases are suspected to be also involved in the degradation of lung structural material. An elastinolytic neutral metalloprotease was purified 320-fold from the extracellular fluid of Aspergilus fumigatus grown on elastin by affinity chromatography on bacitracin-Sepharose 4B and gel filtration on Sephadex G-75. The molecular mass was determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(53 citation statements)
references
References 25 publications
2
49
1
1
Order By: Relevance
“…Accordingly, immunogold localization studies demonstrated that A. fumigatus secretes an elastinolytic metalloprotease into invading lung tissue, and Cry. neoformans has been shown to have proteolytic activity against elastin (Muller & Sethi, 1972;Brueske, 1986;Monod et al, 1993;Markaryan et al, 1994). Although the mechanisms that allow Cry.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, immunogold localization studies demonstrated that A. fumigatus secretes an elastinolytic metalloprotease into invading lung tissue, and Cry. neoformans has been shown to have proteolytic activity against elastin (Muller & Sethi, 1972;Brueske, 1986;Monod et al, 1993;Markaryan et al, 1994). Although the mechanisms that allow Cry.…”
Section: Discussionmentioning
confidence: 99%
“…However, the elution profile by the affinity column and SDS-PAGE of protease indicate that the interaction between bacitracin and protease was specific. Moreover, bacitracin is known in general to interact with proteases in bacitracin affinity chromatography Markaryan et al, 1994;Irvine et al, 1993). Many studies have been published in literature about purification of protease with different methods, as summarized in Table 4.…”
Section: Kinetic Parameters Of Purified Enzymementioning
confidence: 99%
“…Ground-glass shadowing progressing to diffuse alveolar shadowing was rarely described. 28 The duration of AF therapy in IA is problematic, and there is no clear guidance from published literature. Generally, one should continue treatment until resolution of signs and symptoms, clearance of cultures, improvement of radiological manifestations and improve-ment of the host defences that contributed to the infection.…”
Section: Clinical Aspectsmentioning
confidence: 99%